2007
DOI: 10.1080/00365510601051441
|View full text |Cite
|
Sign up to set email alerts
|

Serum ionized magnesium and calcium levels in adult patients with seizures

Abstract: We were able to show significantly lower Mg(2+) and higher ionized Ca(2+)/Mg(2+) ratios in seizure patients compared with a racially matched control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…V). Many studies have found that patients suffering from epilepsy display lower blood Mg 2ϩ values (212,375,482). The link between Mg 2ϩ status and the development of seizures may be explained by the role of Mg 2ϩ in NMDA receptor blockade.…”
Section: Epilepsymentioning
confidence: 99%
“…V). Many studies have found that patients suffering from epilepsy display lower blood Mg 2ϩ values (212,375,482). The link between Mg 2ϩ status and the development of seizures may be explained by the role of Mg 2ϩ in NMDA receptor blockade.…”
Section: Epilepsymentioning
confidence: 99%
“…It has been suggested that low Mg 2+ or altered balance between Mg 2+ and ionized calcium (Ca 2+ ) may precipitate seizures (179). Patients with epilepsy have been shown to have significantly lower mean Mg 2+ levels and an increased Ca 2+ /Mg 2+ ratio in spite of normal total serum Mg levels (180). Mg has been shown to decrease the seizure duration in idiopathic epilepsy with the reduction in duration proportional to the severity of the seizure (181).…”
Section: Novel Treatmentsmentioning
confidence: 99%
“…12 In parallel, there is a direct relationship between the decrease of Mg in myocardial tissue of individuals who died suddenly when compared with those dying of other causes. 10,13 On the whole, although some studies have shown a relationship between serum Mg deficiency and refractory epilepsy in both children and adults, 14,15 our analysis is the first to demonstrate a possible significant risk of SUDEP in individuals with low levels of serum Mg. In this sense, we have to keep in mind that as Mg is a potential modulator of seizure activity (because of its ability to antagonize the excitatory calcium influx through the N-methyl-D-aspartate (NMDA) receptor), 15,16 its serum levels reduction in people with refractory epilepsy can increase the frequency of seizures in these individuals, which is currently considered the most important risk factor for occurrence of SUDEP.…”
Section: Discussionmentioning
confidence: 68%